The Future of urban parks in Europe; The role of landscape architecture in design and research: 1. Design of parks and urban landscapes: 1. Városi parkok és tájak tervezése - van den Toorn, Martin (4D Journal of Landscape Architecture and Garden Art, 2014)
This article is based on a presentation at a conference held in Budapest in 2013. It is part of a series of three articles that gives a broad overview of the design of urban public parks in a European context. This is the first in the series and focuses on design and research of parks and urban landscapes. We start with a short historical overview of urban park development. It sketches a development of gardens and parks as green elements towards the concept of park systems and eventually the creation of urban landscapes. In the second part the actual situation of the urban park is elaborated. This done by taking closer look at an approach basic for landscape architecture; the distinction between different levels of intervention and their design means. Two design approaches specifically for urban park design are further elaborated; urban & suburban, existing & newly designed parks. In the last part the focus is on the relation between design and research. The future and further development of landscape architecture as an academic discipline is predominantly based on research. The great amount of plans that have been made in the past can function as a research base for developing design knowledge which can be developed by systematic analysis of realised plans, nowadays called precedent analysis.